2012
DOI: 10.1007/s12028-012-9673-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Central Sympathetic Activation in Spontaneous Primary Subarachnoid Hemorrhage

Abstract: Central sympathetic activation relates to clinical severity and female gender. No definitive associations were found for age, hemorrhage amount, or aneurysm location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…As previously described, our study showed that the severity of cardiac injury was associated with the degree of catecholamine release in the plasma of our SAH patients [26] in univariate analysis and with the severity of SAH in multivariate analysis. The evolution of echocardiographic and biological markers paralleled the evolution of plasma levels of norepinephrine and epinephrine and returned in most patients toward normal levels within a week.…”
Section: Discussionsupporting
confidence: 76%
“…As previously described, our study showed that the severity of cardiac injury was associated with the degree of catecholamine release in the plasma of our SAH patients [26] in univariate analysis and with the severity of SAH in multivariate analysis. The evolution of echocardiographic and biological markers paralleled the evolution of plasma levels of norepinephrine and epinephrine and returned in most patients toward normal levels within a week.…”
Section: Discussionsupporting
confidence: 76%
“…However, methodological flaws such as the time point and the source of blood samples weakens the validity of this study. The second study could demonstrate a significant relationship of sympathetic activation to female gender and clinical but not to radiological bleeding severity [5]. Based on the same dataset, this group also published data about the acute central sympathetic response after aSAH which does not seem to be related to the development of cerebral VS [15].…”
Section: Discussionmentioning
confidence: 92%
“…In literature only little information is available on the relation of BP course to sympathetic activation in aSAH patients. There is only one study available which analyzed the MAP course during the first 2 days after aSAH and failed to demonstrate a correlation between sympathetic activation and MAP values [5]. However, the validity of these findings remains controversial since BP is usually treated rigorously prior to aneurysm treatment in order to reduce the risk of re-bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations